Efektivitas dan Efisiensi Sistem Informasi Akuntansi serta Pengendalian Internal dalam Pengelolaan Persediaan (Studi kasus di PT. Signal Niaga Indonesia) - Wany, Eva Wany; Lestari, Dinda Putri (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2025)
This research aims to determine the effectiveness and efficiency of the accounting information system and internal control in inventory management at PT. Signal Niaga Indonesia which is located on Jl. Raya Banjarsugihan 15B. The methodology used is qualitative research with an interview, observation and documentation approach to collect data related to inventory management practices. The phenomenon identified is a lack of accuracy in the recording process which results in stock shortages and excesses. Internal control at this company is carried out through the FIFO (First In, First Out) method and monthly stock taking, as well as additional monitoring using CCTV to ensure data accuracy. Although the implemented system shows potential in improving efficiency, obstacles such as excess stock and administrative errors remain significant challenges. The results of this research conclude that to increase the effectiveness of accounting information systems and internal control, increased accuracy in recording and training for employees is needed. Recommendations for improvement include the implementation of more advanced technology and stricter procedures in inventory management.